2010
DOI: 10.5212/publ.exatas.v.16i1.0004
|View full text |Cite
|
Sign up to set email alerts
|

Qualidade Fisiológica De Sementes De Feijão Envelhecidas Em Condições De Alta Temperatura E Umidade Relativa

Abstract: RESUMOO feijão comum é um alimento tradicional da alimentação humana e durante o armazenamento das sementes ocorre perda de qualidade, cujo grau de intensidade depende de diferentes fatores. Assim, o objetivo deste trabalho é avaliar os efeitos do armazenamento em condições controladas de alta temperatura e umidade relativa na qualidade da semente do feijão. Foram utilizadas sementes da variedade do Uirapuru e Rio Vermelho, armazenadas a 40 ºC e 76 % de umidade relativa, e amostras retiradas aos zero (controle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 2 publications
0
2
0
1
Order By: Relevance
“…Vários tipos de feijão comum são cultivados no Brasil, dentre eles o carioca, o preto e os especiais, em três safras no ano. Esse cenário demonstra a relevância socioeconômica desta cultura para o Brasil, cultivado por pequenos e grandes produtores (AVACI et al, 2010). A qualidade da semente é expressa pela interação de quatro componentes: genético, físico, fisiológico e sanitário.…”
Section: Introductionunclassified
“…Vários tipos de feijão comum são cultivados no Brasil, dentre eles o carioca, o preto e os especiais, em três safras no ano. Esse cenário demonstra a relevância socioeconômica desta cultura para o Brasil, cultivado por pequenos e grandes produtores (AVACI et al, 2010). A qualidade da semente é expressa pela interação de quatro componentes: genético, físico, fisiológico e sanitário.…”
Section: Introductionunclassified
“…Maia et al (2011) includes the influence of genetic variability associated with germination and emergence among white bean strains. Reduction on seed germination percentage of two bean varieties submitted to storage was also observed by Avaci et al (2010). Santos et al (2005) evaluated the behavior of bean cultivars during 8-months storage, noticing that 80% of samples presented a linear decrease in germination.…”
Section: Journal Of Agricultural Sciencementioning
confidence: 99%
“…In this study, stored bean seeds lost physiological quality, this alteration probably derived from a higher intensity of cell membrane system disruption (Rigueira et al, 2009) observed in bean seeds stored for 120 days, as time passed by. Avaci et al (2010) analyzed physiological quality of two bean varieties during 30-days storage for what time provided higher electrical conductivity in seeds, increasing seed damage. Opposite results were found by Cassol et al (2012) who observed no significant difference between storage times of 0 and 90 days in bean seeds.…”
Section: Journal Of Agricultural Sciencementioning
confidence: 99%